Gender‐specific risk factors for low bone mineral density in patients taking antipsychotics for psychosis. (8th January 2018) - Jhon, Min; Yoo, Taeyoung; Lee, Ju‐Yeon; Kim, Seon‐Young; Kim, Jae‐Min; Shin, Il‐Seon; Williams, Lana; Berk, Michael; Yoon, Jin‐Sang; Kim, Sung‐Wan
Abstract: Objective: This study examined clinical and gender‐specific risk factors for low bone mineral density (BMD) in adult patients with psychotic disorders. Methods: The study included 285 community‐dwelling patients with psychotic disorders. Dual‐energy X‐ray absorptiometry was used to measure BMD. Clinical characteristics associated with low BMD were identified with logistic regression analysis in total population and each gender. Results: Fifty‐eight (20.4%) subjects had low BMD. Low BMD was more common in men and in patients with low body mass indices (BMIs), as well as in those with shorter treatment durations, those on Medicaid, and patients using serotonergic antidepressants. Logistic regression analysis revealed that low BMD was negatively associated with BMI and treatment duration and positively with gender (male) and serotonergic antidepressants use in the overall population. In men, low BMD was associated with treatment duration and BMI; in women, low BMD was associated with BMI, prolactin level, vitamin D, and serotonergic antidepressant use. Conclusion: Managing the risk factors associated with low BMD among patients with psychotic disorder should be done gender‐specifically. Psychotropic agents should be prescribed mindful of their effects on bone, as use of these medications is a modifiable risk factor for osteoporosis in women with psychotic disorders.